Aspiration and cytological evaluation of idiopathic bone cavities of the jaw. Issue 3 (June 2017) - Rivero, Elena Riet Correa; Daltoé, Felipe Perozzo; Mello, Fernanda Weber; de Souza, Carlos Eduardo Chrzanowski Pereira; Grando, Liliane Janete
Highlights: Cell blocks prepared from fine-needle aspirations allow the cytological evaluation of IBC content. The main finding of cytological evaluation of IBC is the presence of fibrin arranged as a net. The cytological evaluation is an important tool to establish the diagnosis of IBCs of the jaw. Abstract: The idiopathic bone cavity (IBC) is an intraosseous pseudocyst devoid of epithelial lining. Clinically, IBCs of the jaw are asymptomatic and normally found in routine radiographic exams. Although the literature regarding the content of IBCs is controversial, the final diagnosis is usually aided by the discovery of an empty cavity upon surgical exploration. The aim of this study was to perform cytological and histological analysis of IBC contents. Cytological analysis of nine cases of IBC was performed after puncture and processed by the cell block technique. Histological analysis was performed in six cases in which it was possible to collect enough material by curettage of bone walls. Remarkably, cell block analysis revealed the presence of fibrin, often arranged as a net; erythrocytes; and inflammatory cells, with a predominance of lymphocytes as well as some macrophages and neutrophils. Histological analysis showed the presence of scant connective tissue, bone trabeculae, hemorrhagic foci, and hemosiderin. Only two cases presented scattered multinucleated giant cells. Cytological evaluation of IBC content by the cell block technique might represent a useful diagnostic tool, especially in cases in which there is no available material for curettage in the cavity.